2023
DOI: 10.1557/s43578-022-00873-y
|View full text |Cite|
|
Sign up to set email alerts
|

Resolving intragranular stress fields in plastically deformed titanium using point-focused high-energy diffraction microscopy

Abstract: The response of a polycrystalline material to a mechanical load depends not only on the response of each individual grain, but also on the interaction with its neighbors. These interactions lead to local, intragranular stress concentrations that often dictate the initiation of plastic deformation and consequently the macroscopic stress–strain behavior. However, very few experimental studies have quantified intragranular stresses across bulk, three-dimensional volumes. In this work, a synchrotron X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…This application example shows that our rare event detection framework can track changes to the diffraction peaks induced by crystallographic slip and can detect small changes to the incident beam flux. This is particularly useful for newer FF-HEDM modes that require much longer scan time (on the order of several hours) such as stitching HEDM (Johnson et al, 2023) (where multiple field-of-view scans across a sample cross section are stitched to interrogate a sample cross section larger than the beam size available at the endstation) or point focus HEDM (Li et al, 2023) (where multiple scans across a sample cross section are conducted with a 2D focused beam to acquire intra-granular microstructure and micromechanical state information). REI can be an independent metric indicating changes to the FF-HEDM patterns due to incident beam characteristic changes or material state changes (such as creep or relaxation) during these scanning techniques.…”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…This application example shows that our rare event detection framework can track changes to the diffraction peaks induced by crystallographic slip and can detect small changes to the incident beam flux. This is particularly useful for newer FF-HEDM modes that require much longer scan time (on the order of several hours) such as stitching HEDM (Johnson et al, 2023) (where multiple field-of-view scans across a sample cross section are stitched to interrogate a sample cross section larger than the beam size available at the endstation) or point focus HEDM (Li et al, 2023) (where multiple scans across a sample cross section are conducted with a 2D focused beam to acquire intra-granular microstructure and micromechanical state information). REI can be an independent metric indicating changes to the FF-HEDM patterns due to incident beam characteristic changes or material state changes (such as creep or relaxation) during these scanning techniques.…”
Section: Figure 12mentioning
confidence: 99%
“…For instance, in an in situ HEDM experiment where a sample is subject to various levels of mechanical loading to study the material response heterogeneity at the mesoscale, the levels at which the loading is paused -to deploy a higher-resolution and more beamtimeconsuming characterization method -are often decided according to macroscopic milestones such as yield strength in the macroscopic stress-strain curve of the material. Alternatively, such experimental decisions to be made on the fly may require heroic efforts during time-limited beam access to reduce the full HEDM data set and identify when the scientifically interesting phenomena occur (Naragani et al, 2017;Ravi et al, 2021;Suter et al, 2008;Li et al, 2023;Maddali et al, 2020;Simons et al, 2015). Hence, a high level of reliable automation is desirable and crucial for a successful study.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to type II stresses compared with type I stresses, intragranular (type III) stresses may deviate from grain-averaged type II stresses [17][18][19][20][21][22][23][24]. Recently, the evaluation of type III stresses has been achieved using a 3DXRD modality termed scanning 3DXRD (also called point-focused HEDM) with a monochromatic point-focused (pencil) beam [25][26][27]. In scanning 3DXRD, a voxel-resolved stress tensor with a voxel size smaller than a grain size can be obtained by illuminating a pencil beam and rotating a sample.…”
Section: Introductionmentioning
confidence: 99%
“…Grain mapping with grain boundaries can be achieved by a three-dimensional scan of a sample, including sample rotations at the expense of measurement time [28]. Unsurprisingly, voxel-resolved stresses showed deviations from grain-averaged stresses in a plastically deformed metal and alloy [27,29]. It was also shown that deviation exceeded macroscopic tensile strength and voxel-resolved stresses were in highly triaxial stress states even under uniform elongation.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, nondestructive 3D OM and strain mapping for polycrystalline alloys have been achieved using synchrotron-based X-ray diffraction (XRD) and imaging methods, such as differential aperture X-ray microscopy (DAXM) [5][6][7][8][9][10][11][12][13], diffraction contrast tomography (DCT) [14][15][16][17][18][19][20], 3D XRD microscopy (3DXRD) , high-energy diffraction microscopy (HEDM) , and scanning 3DXRD [67][68][69][70][71][72][73][74][75][76][77]. DAXM uses a focused polychromatic X-ray beam and a far-field area detector to obtain Laue diffraction patterns from multiple grains.…”
Section: Introductionmentioning
confidence: 99%